Behavior of Cu-In-Te Electrodeposition from Acid Solution - Takahiro Ishizaki; Nagahiro Saito; Daisuke Yata; Akio Fuwa (The Minerals, Metals and Materials Society, 2000)
"Ternary compound-semiconductor, CuInTe2, film was deposited cathodically under potentiostatic conditions on titanium substrate from aqueous solution containing CuCl2, InCl3, TeO and HCI in this study.The deposition parameters such as electrolytic solution composition, potential and temperature were optimized· for electrodeposition of CulnTe2. Structural characterization of the: deposited film was also carried out using XRD and SEM. Electrodeposited films Were prepared and analyzed for their chemical composition using ICP. The ICP analyses showed that the stoichiometry of the films could be controlled by (1) the deposition potential and/or by (2) the electrolytic bath composition.1. IntroductionThe ternary chalcopyrite type compound semiconductors exhibit such electrical, chemical and optical properties that make them promising for photovoltaic devices (Kazmerski and Wagner 1985)(1). Many researches have been devoted to the characterization of these materials for over one and a half decades. High efficiency solar cells based on p-CulnSe2/n-CdS have been reported (Mickelson and Chen 1983)(2).The electrodeposited fil ns of semiconductors have more advantage than other physical and chemical deposition techniques; it is relatively easy and economic technique and the semiconducting properties such as band-gap variation, concentration of dopant stoichiometric composition and so on can be controlled with some accuracy. The electrodepositions of the ternary CuInS2, CulnSe2 have been reported by many workers (Hodes and Cahen 1986, Bhattachaya 1983, Singh et al 1986, Lokhande and can be prepared as both p-type and n-type. Therefore, its potential for application in optical and photovoltaic devices is one of the great interests. Bhattacharaya and Rajeshwar (1986)(9) reported the electrodeposition of CuInTe2 from an acidic bath· on indium tin oxide (ITO) and Mo substrate. Triethanolamine (TEA) was used as a complexing agent for indium. The electrodeposited CuInTe2 films were non-stoichiometric in composition under all their experimental conditions by electron-probe micro analysis (EPMA) and Auger depth profile analysis. In this paper, we report our results on the behavior .of Cu-In-Te electrodeposition from ·acidic baths; the preparation of CulnTe2 and the effect of bath composition on electrodeposited films obtained."